Motivations and barriers to pursue cancer genomic testing: A systematic review. Issue 6 (June 2021) - Smith-Uffen, Megan; Bartley, Nicci; Davies, Grace; Best, Megan
Highlights: Consumers are interested in cancer genomic testing if it gives actionable results. Ability to predict risk, inform management, benefit families are motivators to test. Patients are concerned about cost, confidentiality, utility, psychological harm. Providers must educate and manage patient expectations of testing. Abstract: Objectives: Single-gene testing is associated with psycho-social challenges for cancer patients. Genomic testing may amplify these. The aim of this study was to understand patients' motivations and barriers to pursue cancer genomic testing, to enable healthcare providers to support their patients throughout the testing process and interpretation of test results. Methods: Five databases were searched for original peer reviewed research articles published between January 2001 and September 2018 addressing motivation for genomic cancer testing. QualSyst was used to assess quality. Results: 182 studies were identified and 17 were included for review. Studies were heterogenous. Both somatic and germline testing were included, and 14 studies used hypothetical scenarios. 3249 participants were analyzed, aged 18 to 94. Most were female and white. The most common diagnoses were breast, ovarian, lung and colorectal cancer. Interest in testing was high. Motivations included ability to predict cancer risk, inform disease management, benefit families, and understand cancer. Barriers included concerns about cost, privacy/confidentiality, clinical utility, and psychological harm. Conclusions: Despite concerns, consumers are interested in cancer genomic testing if it can provide actionable results for themselves and their families. Practice Implications: Providers must manage understanding and expectations of testing and translate genetic information into health-promoting behaviours.